Mengembangkan Kemampuan Mengenal Huruf Abjad Melalui Media Bungkus Snack pada Anak Kelompok Bermain Pelita Hati - Mahzuna, Elvyana La’alil; Ridwan, Ridwan; Khan, Rosa Imani (Penerbit Widina, Widina Media Utama, 2023)
This research is motivated by the results of observations and experiences of researchers, that the ability to recognize the letters of the alphabet of students is still very low. The activeness of children in the process of learning to recognize the letters of the alphabet is also lacking. Lack of children's activity in the learning process is very influential on the development and learning outcomes of students. The learning strategies that have been used by teachers so far have not attracted children's interest, so that in the learning process children feel bored. The purpose of carrying out this research was to develop the ability to recognize letters of the alphabet using snack packs for students in group B KB Pelita Hati, Sidem Village, Gondang District, Tulungagung Regency, for the 2022/2023 academic year. This study used a Classroom Action Research (PTK) approach with 12 students in group B KB Pelita Hati, Sidem Village, Gondang District, Tulungagung Regency, for the 2022/2023 academic year, consisting of 5 boys and 7 girls. This research was conducted in two cycles, using instruments in the form of children's performance assessment sheets teacher observation sheets in learning activities. Each cycle is carried out in 1 meeting, covering the stages of planning, implementing, observing and reflecting. The conclusion of the results of this study is that learning using snack pack media is proven to be able to develop the ability to recognize letters of the alphabet in group B students of Pelita Hati KB Sidem Village, Gondang District, Tulungagung Regency for the 2022/2023 Academic Year. The percentage of learning completeness in Cycle I was 58.3% then rose to 75% in Cycle II.ABSTRAKLatar belakang dari penelitian ini dihasilkan dari pengamatan dan pengalaman peneliti, bahwa kemampuan mengenal huruf abjad anak didik masih sangat rendah. Keaktifan anak pada proses pembelajaran mengenal huruf abjad juga masih kurang. Kurangnya keaktifan anak dalam proses pembelajaran ini sangat berpengaruh terhadap perkembangan dan hasil belajar anak didik. Strategi pembelajaran yang selama ini digunakan oleh guru kurang menarik minat anak, sehingga dalam proses pembelajaran anak merasa bosan. Tujuan dilaksanakannya penelitian ini adalah untuk mengembangkan kemampuan mengenal huruf abjad menggunakan media bungkus snack pada anak didik kelompok B KB Pelita Hati Desa Sidem Kecamatan Gondang Kabupaten Tulungagung Tahun Pelajaran 2022/2023. Pada penelitian ini menggunakan metode pendekatan Penelitian Tindakan Kelas (PTK) dengan subyek penelitian 12 anak didik kelompok B KB Pelita Hati Desa Sidem Kecamatan Gondang Kabupaten Tulungagung Tahun Pelajaran 2022/2023, yang terdiri dari 5 anak lali-laki dan 7 anak perempuan. Penelitian ini dilaksanakan dalam dua siklus, menggunakan instrumen berupa lembar penilaian unjuk kerja anak lembar observasi guru dalam kegiatan pembelajaran. Masing-masing siklus dilaksanakan dalam 1 pertemuan, meliputi tahap perencanaan, pelaksanaan, observasi dan refleksi. Ikhtisar dari hasil penelitian ini adalah proses pembelajaran menggunakan media bungkus snack terbukti dapat mengembangkan kemampuan mengenal huruf abjad pada anak didik kelompok B KB Pelita Hati Desa Sidem Kecamatan Gondang Kabupaten Tulungagung Tahun Pelajaran 2022/2023. Persentase ketuntasan belajar pada Siklus I sebesar 58,3% kemudian naik menjadi 75% pada Siklus II.